Therapie der Mycosis fungoides und des Sézary-Syndroms - Nicolay, Jan Peter; Assaf, Chalid (Der Hautarzt, 2017)
Adequate therapeutic management of cutaneous T-cell lymphoma (CTCL) requires the identification of the exact CTCL stage and entity within the current WHO classification. There is no curative therapy for CTCL yet, so that treatment currently aims at improving symptoms and quality of life as well as reducing relapse rates. The treatment has to be stage-adapted. Therapeutic options comprise skin-directed as well as systemic treatment. In early stages, phototherapy and local steroids are the first-line therapeutic options. For the therapy of higher stages, interferon alpha and the RXR-specific retinoid bexarotene are used as first-line medications. Second-line treatment comprises monochemotherapy with agents like gemcitabine or liposomal doxorubicine. Nevertheless, the high relapse rates in higher stages make novel alternative treatment options necessary. As future therapy, especially the fusion protein brentuximab-vedotin directed against CD30 shows promising potential in clinical studies.
Gesehen am 03.05.2018